AMIDATION REACTION OF MYRISTIC ACID WITH DIETHANOLEAMINE - Salieva , Gulrukh; Kenjabaev, Ulugbek; Kholiqov , Tursunali; Matchanov , Alimzhan (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
Diethanolamine (DEA) is used in many reactions, mainly in the synthesis of heterocyclic compounds, for example, morpholines, piperazines, oxazolidines, dioxazosines, crawn ethers and ionic liquids. The reaction of fluoroalkene derivatives with diethanolamine produces eight-memebered dioxazocines. Amine-containing eight-membered cyclic boronic esters could be successfully obtained from diethanolamine and boron derivatives. The purpose of the work is to carry out the reaction of diethanolamine with myristic acid and to determine the physico-chemical and spectral properties of the reaction products.